KEHIDUPAN PENGAMEN JALANAN DI KAWASAN BOULEVARD KOTA MANADO - Kembuan, Tabita Yudea; Matheosz, Jenny Nelly; Pratiknjo, Maria Heny (Universitas Sam Ratulangi, 2021)
Living in the city is certainly not easy, especially with the characteristics of urban communities that are individualistic causing competition from each other in obtaining a job, while the available jobs must be adapted to sufficient educational skills and skills. One of the most favorite jobs run by people who don't have a permanent job is to be a busker either individually or in groups because it's easy to earn money.Busking is a fun activity for them because by busking they can channel their hobbies and talents in the field of art. Busker grows up with various social backgrounds, such as broken home children, orphans who are wasted, children whose birth is not desired, or children who have to help the economy of their parents and children who run away from various problems of their families and communities.The daily activities of street buskers in Manado city can be seen everywhere, starting in restaurants, in shop houses, in market 45, and other crowded places.The fate of the complainant is very unfortunate, many times got a rejection that disappointed them. There are still some who accept well the arrival of the buskers. The scorching heat of the sun is felt to sting their skin, more irony if there is a raid conducted by officers SatPol PP Manado City, if their luck is good they can escape the raids of the officers.Â Keywords: buskers, poverty, livelihoods